The drug taking and the treatment in patients that are involved in illegal activities - Sanabria Carretero, Manuel (2001)
The study focuses on the assessment of the implications that criminal behavior has, not only at the start of treatment for drug taking but also during its development and results. With this aim in mind a sample of 209 patients who had applied for treatment were selected and assessed inthe principal object areas of analysis over a period of ayear anda half at six monthly intervals.The results indicate that time spent in a therapeutic centre significantly reduces criminal behaviour. However, those patients with a greater past history present more difficulties and give a poorer initial response, although during the period of follow-up these differences tend to disappear.